Analisis Terjadinya Korosi pada Pesawat Seaplane Amphibian Cessna 172 SP Menggunakan Fishbone di Api Banyuwangi - Sabrina Analisristianti; Andung Luwihono; Kukuh Tri Prasetyo; I Made Dwi Surya Dharma; Sabam Danny Sulung (Pusat riset dan Inovasi Nasional, 2025)
Amphibian Cessna 172 SP is an aircraft designed to operate in aquatic environments and is frequently exposed to seawater, which is highly corrosive. Such exposure poses a serious issue of corrosion affecting both the structure and components of the aircraft, particularly the floats, lower fuselage, and propeller. Corrosion not only reduces the quality and integrity of the material but also potentially compromises flight safety and increases maintenance costs. This study aims to analyze the causes of corrosion on the Seaplane Amphibian Cessna 172 SP using the fishbone diagram to identify the main contributing factors, including material, method, environment, manpower, and machine. In addition, the 5W+1H approach is employed to examine the problem in greater detail and develop preventive strategies. The results of the analysis indicate that the dominant factors causing corrosion are the high intensity of direct contact with seawater, suboptimal cleaning processes due to limited manpower, and the use of cleaning agents not fully compatible with aircraft materials. Mitigation efforts include implementing more effective cleaning procedures, applying anti-corrosion chemicals such as AeroShell Fluid 41, Bonderite Turco S.S.2, Ardrox AV-15, CorrosionX, Toolmates Dry Film Lubricant 6075, and Ultra Tef-Gel, as well as conducting scheduled inspections at specific intervals. This research is expected to provide more appropriate preventive strategies to extend the service life of the aircraft structure while maintaining both operational safety and efficiency.